Evaluating the impact resistance of roller compacted concrete containing crumb rubber and nanosilica using response surface methodology and Weibull distribution. (8th April 2019) - Adamu, Musa; Mohammed, Bashar S.; Liew, Mohd Shahir; Alaloul, Wesam Salah
Abstract : Purpose: Roller compacted concrete (RCC) pavement is used in areas subjected to heavy impact loads; therefore, higher impact resistance is a desirable property of consideration. This study aims to investigate the effect of partial replacement of fine aggregate with crumb rubber (CR) and the addition of nanosilica (NS) by weight of cementitious materials on the impact resistance of roller compacted rubbercrete (RCR). Design/methodology/approach: Four replacement levels of CR (0, 10, 20 and 30 per cent) and four addition levels of NS (0, 1, 2 and 3 per cent) were considered. The impact resistance test was carried out using the drop weight test recommended by ACI 544. Findings: The results showed that the impact resistance of RCR increases with an increase in both CR and NS addition, though for CR above 20 per cent, sudden drop in impact resistance was observed. However, NS reduces the ductility of RCR by decreasing the post-cracking impact resistance. Response surface methodology was used to develop models for predicting the impact resistance of RCR, and the developed models showed a high degree of correlation. As a result of wide variations in the impact drop test data, two-parameter Weibull distribution function was used for the data analysis, and it was found that the probabilistic distributions of the first crack and ultimate failure impact resistance follow the two-parameter Weibull distribution function. Originality/value: In this work, the effect of partial replacement of fine aggregate with CR and the addition of NS by weight of cementitious materials on the impact resistance of RCC pavement has been investigated. CR has been used to increase the impact resistance of RCC Pavement.